Reina Ramos works it out! - Otheguy, Emma (I can read book., 2022)
"Reina Ramos is excited about dressing up as Frida Kahlo for the class wax museum. Frida was a strong person like Reina's mami and abuela. But when her best friend, Nora, picks Frida instead, Reina doesn't know what to do. Who will she dress up as now?"--